Shotgun metagenome guided exploration of anthropogenically driven resistomic hotspots within Lonar soda lake of India - Chakraborty, Jaya; Sapkale, Vibhavari; Rajput, Vinay; Shah, Manan; Kamble, Sanjay; Dharne, Mahesh (Ecotoxicology and Environmental Safety, 2020)
Anthropogenic activities mediated antibiotic resistance genes (ARGs) in the pristine aquatic bodies (lakes) is raising concern worldwide. Long read shotgun sequencing was used to assess taxonomic diversity, distribution of ARGs and metal resistance genes (MRGs) and mobile genetic elements (MGEs) in six sites within hypersaline Lonar soda lake (India) prone to various anthropogenic activities. Proteobacteria and Euryarchaeota were dominant phyla under domain Bacteria and Archaea respectively. Higher abundance of Bacteroidetes was pragmatic at sites 18LN5 and 18LN6. Functional analysis indicated 26 broad-spectrum ARGs types, not reported earlier in this ecosystem. Abundant ARG types identified were multidrug efflux, glycopepetide, bacitracin, tetracycline and aminogylcoside resistance. Sites 18LN1 and 18LN5 depicted 167 and 160 different ARGs subtypes respectively and rpoB2, bcrA, tetA(48), mupA, ompR, patA, vanR and multidrug ABC transporter genes were present in all samples. The rpoB2 gene was dominant in 18LN1, whereas bcrA gene in 18LN2-18LN6 sites. Around 24 MRGs types were detected with higher abundance of arsenic in 18LN1 and copper in 18LN2-18LN6, signifying metal contamination linked to MRGs. The bacterial taxa Pseudomonas, Thioalkalivibrio, Burkholderia, Clostridium, Paenibacillus, Bacillus and Streptomyces were significantly associated with ARGs. This study highlights the resistomic hotspots in the lake for deploying policies for conservation efforts.
Keywords: ARGs; diversity; Lonar lake; MGEs; MRGs; Nanopore sequencing